DEGRADASI SENYAWA PARAQUAT DALAM PESTISIDA GRAMOXONE SECARA SONOLISIS DENGAN PENAMBAHAN ZnO - Febrina Arfi; Safni Safni; Zaimi Abdullah (UIN AR-RANIRY, 2015)
Degradation of paraquat in gramoxone pesticide had been done by sonolysis with adding ZnO. Sonolysis method were performed using an ultrasound with frequency 50 kHz. The optimum condition of sonolysis were found at temperature 40oC. The percentage of degradation of 20 mg/L paraquat by sonolysisi method without adding ZnO during 120 minutes treatment was 20,70%, and with adding0,08 g percentage of degradation increasesd to 56,83% at the same treatment.